Efficacy of TIPS plus extrahepatic collateral embolisation in real-world data: a validation study - Chao Chen; Feng Zhang; Hao Wu; Wei Wu; Hui Xue; Yuzheng Zhuge; Chunqing Zhang; Guangchuan Wang; Zhengjie Li; Qiong Wu; Bo Wei; Jun Tie; et al. (BMJ Open Gastroenterology)
Objectives The efficacy of transjugular intrahepatic portosystemic shunt (TIPS) plus extrahepatic collateral embolisation (TIPS+E) in reducing rebleeding and hepatic encephalopathy (HE) post-TIPS was recently reported in a meta-analysis, but further validation is essential. This study aims to confirm the effectiveness of TIPS+E using real-world data.Methods The multicentre retrospective cohort included 2077 patients with cirrhosis who underwent TIPS±E (TIPS: 631, TIPS+E: 1446) between January 2010 and December 2022. Regression and propensity score matching (PSM) were used to adjust for baseline characteristic differences. After PSM, clinical outcomes, including rebleeding, HE, survival and further decompensation (FDC), were analysed. Baseline data from all patients contributed to the construction of prognostic models.Results After PSM, 1136 matched patients (TIPS+E: TIPS=568:568) were included. TIPS+E demonstrated a significant reduction in rebleeding (HR 0.77; 95% CI 0.59 to 0.99; p=0.04), HE (HR 0.82; 95% CI 0.68 to 0.99; p=0.04) and FDC (HR 0.85; 95% CI 0.73 to 0.99; p=0.04), comparing to TIPS. Significantly, TIPS+E also reduced rebleeding, HE and FDC in subgroup of using 8 mm diameter stents and embolising of gastric varices+spontaneous portosystemic shunts (GV+SPSS). However, there were no differences in overall or subgroup survival analysis. Additionally, the random forest models showed higher accuracy and AUROC comparing to other models. Controlling post-TIPS portal pressure gradient (pPPG) within 7 mm Hg<pPPG<8.5 mm Hg improved prognosis, especially in TIPS+E group.Conclusion Our real-world data validation confirms the high efficacy of TIPS+E in reducing rebleeding and HE, particularly when using 8 mm diameter stents, embolising GV+SPSS and maintaining an optimal pPPG.